E. Lucas Bridges, Ultimo confine del mondo. Viaggio nella Terra del Fuoco (Altre Modernità, 2011)
E. Lucas Bridges, Ultimo confine del mondo. Viaggio nella Terra del Fuoco.(Torino, Einaudi, 2009, ISBN 9788806197582, XX- 590 pp.)